2020
DOI: 10.1093/jamia/ocaa154
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning–based clinical decision support system to identify prescriptions with a high risk of medication error

Abstract: Objective To improve patient safety and clinical outcomes by reducing the risk of prescribing errors, we tested the accuracy of a hybrid clinical decision support system in prioritizing prescription checks. Materials and Methods Data from electronic health records were collated over a period of 18 months. Inferred scores at a patient level (probability of a patient’s set of active orders to require a pharmacist review) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 20 publications
0
67
0
12
Order By: Relevance
“…The redundancy of alerts has also led to an increase in alerts and a decrease in the rate of PI, although the pharmacist analyzed actually all these alerts. Using supervised machine learning for optimization or for creation of rules demonstrated promising results in improving specificity of alerts [7,8]. During the first period, the number of alerts changed significantly, from 7 to 40 alerts to be assessed per day (all rules included).…”
Section: Discussionmentioning
confidence: 99%
“…The redundancy of alerts has also led to an increase in alerts and a decrease in the rate of PI, although the pharmacist analyzed actually all these alerts. Using supervised machine learning for optimization or for creation of rules demonstrated promising results in improving specificity of alerts [7,8]. During the first period, the number of alerts changed significantly, from 7 to 40 alerts to be assessed per day (all rules included).…”
Section: Discussionmentioning
confidence: 99%
“…One paper describes the use of electronic health records to support a public health response to the COVID-19 pandemic with a focus on academic centers in the United States [ 5 ]. Other papers focus on the integration of Artificial Intelligence (AI) and machine learning-based with clinical decision support system to help in different clinical situations [ 6 ].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…This hybrid model using knowledge-driven (expert system) and date-driven approaches (machine learning) has shown to be an accurate tool at intercepting potential prescription errors. The accuracy of this hybrid decision support algorithm showed a sensitivity of 0.81 (95% CI, 0.78-0.84) and a precision 0.75 (95% CI, 0.70-0.80), that outperformed classic prescription order analysis tools [9]. Currently used in practice, this tool helps pharmacists to prioritize their medication review activity by distinguishing low and high risk prescriptions.…”
Section: Introductionmentioning
confidence: 94%
“…The score was related to the probability for the prescription to require a pharmaceutical intervention (PI), 10 being the higher probability of containing a medication error leading to a PI. The cut-off score of 2.4 was used to classify the prescriptions as "low risk" if strictly inferior to 2.4, or "high risk" if higher or equal to 2.4, as the result of the original research on the tool development, which showed that this cut-off score maximized the harmonic mean of precision and recall of the tool [9].…”
Section: A Hybrid Decision Support Systemmentioning
confidence: 99%